Sharia Development Strategy in a Sustainable Economy in Surabaya - Rohmah, Ainun Nafisatur; Safier, Muhammad Haykal; Hasanah, Syariatul (Universitas Gorontalo, 2025)
Surabaya has a strategic role for the national priority scale in a sustainable economy, especially in East Java. This research aims to provide an in-depth understanding of sharia development strategies that can overcome various economic challenges faced by the city of Surabaya. Thus, through the analysis of sharia development strategies in the context of the economy in Surabaya, it is hoped that this research can provide new insights for readers and the public in advancing a sustainable economy in this city. The method used in this research is qualitative research, with a library research approach that uses books and other literature as the main material for information about the object of research and theories relevant to the problem in the research.